Efficacy of Tadalafil in Penile Rehabilitation Started Before Nerve-Sparing Robot-Assisted Radical Prostatectomy: A Double-Blind Pilot Study. Issue 3 (6th April 2022) - Noh, Tae Il; Shim, Ji Sung; Kang, Sung Gu; Cheon, Jun; Lee, Jeong Gu; Kang, Seok Ho
Abstract: Background: Despite the widespread practice of nerve-sparing robot-assisted radical prostatectomy (nsRARP) for the treatment of localized prostate cancer (PCa), erectile dysfunction remains a significant sequela of radical prostatectomy. Aim: This study aimed to compare the efficacy of tadalafil 5 mg once daily for erectile function recovery in patients who underwent nsRARP according to the timing of rehabilitation initiation. Methods: In this double-blind, prospective pilot study, a total of 41 patients who underwent nsRARP were randomly assigned into 2 groups according to the timing of rehabilitation initiation. In the preRARP group (n = 20), tadalafil was started 2 weeks before nsRARP, and in the postRARP group (n = 21), it was started 4 weeks after nsRARP. Erectile function recovery after nsRARP was defined as an International Index of Erectile Function (IIEF-5) score of ≥17. Outcomes: The measures of EF recovery were the changes in IIEF-5 score. Results: The rate of erectile function recovery at 12-month follow-up was 80.0% and 71.4% in the preRARP and postRARP groups, respectively. The mean differences between baseline and postoperative IIEF-5 scores at 1-, 3-, 6-, and 12-month follow-up were −11.7 ± 3.2, −7.4 ± 3.2, −5.6 ± 1.5, and −4.1 ± 1.1 in the preRARP group and −14.7 ± 4.7, −12.0 ± 5.0, −9.7 ± 3.9, and −6.0 ± 3.1 in the postRARP group, respectively (1-month, P = .259; 3-months, P = .077; 6-months, P = .014; 12-months, P = .007). Clinical implications: Preoperative tadalafil 5 mg once a day could be used effectively and safely as a strategy for penile rehabilitation after nsRARP. Strengths and Limitations: This study is the first prospective trial of penile rehabilitation with tadalafil 5 mg once a day prior to nsRARP. This is a pilot study with the limitations of a small sample; further and large-scale studies with multiple cohorts, such as an untreated control group and an early immediate rehabilitation group for EF recovery, are needed. Conclusion: This study suggests that preoperative penile rehabilitation using tadalafil may lead to better erectile function recovery than postoperative penile rehabilitation using tadalafil.